2015
DOI: 10.1179/1743284714y.0000000686
|View full text |Cite
|
Sign up to set email alerts
|

Nano-AlN particle reinforced Mg composites: Microstructural and mechanical properties

Abstract: In this study, nano-AlN particles were introduced into pure Mg matrix through the powder metallurgy technique incorporating microwave assisted two-directional sintering followed by hot extrusion. The effect of varying volume fraction of nano-AlN addition on the microstructural and mechanical properties of pure Mg was investigated. Microstructural characterisation revealed marginal grain refinement due to the fairly uniform distribution of AlN nano-particulates. X-ray diffraction results indicated basal texture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…In this respect, the Mg-metal matrixes of the AZ and AM series are the most used in the automotive industry [24]. Reported reinforcement particles introduced in the Mg-MMCs are carbides (SiC, B 4 C, and ZrC) [25][26][27], oxides (Al 2 O 3 , Y 2 O 3 , and TiO 2 ) [28][29][30], borides (TiB 2 ) [31], nitrides (Si 3 N, AlN, ZrN, and TiN) [27,[32][33][34][35][36][37][38][39][40][41][42], carbon nanotubes [43], and metals (Cu, Ti, Mo, and Bi) [44][45][46][47]. For the manufacture of MMCs, different fabrication techniques have been used [48,49].…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, the Mg-metal matrixes of the AZ and AM series are the most used in the automotive industry [24]. Reported reinforcement particles introduced in the Mg-MMCs are carbides (SiC, B 4 C, and ZrC) [25][26][27], oxides (Al 2 O 3 , Y 2 O 3 , and TiO 2 ) [28][29][30], borides (TiB 2 ) [31], nitrides (Si 3 N, AlN, ZrN, and TiN) [27,[32][33][34][35][36][37][38][39][40][41][42], carbon nanotubes [43], and metals (Cu, Ti, Mo, and Bi) [44][45][46][47]. For the manufacture of MMCs, different fabrication techniques have been used [48,49].…”
Section: Introductionmentioning
confidence: 99%
“…The influence of different reinforcements (single type) and processing methods on Mg-based MMCs have been studied, and it has been found that ceramic reinforcements, such as alumina (Al 2 O 3 ) and silicon carbide (SiC) can provide excellent high-temperature properties as well as unique mechanical properties [8][9][10]. Mg-based MMCs containing micro-ceramic reinforcements were succeeded by Mg nanocomposites as a result of the latter's reduced ductility and the former's lower fracture toughness [11][12][13][14][15][16][17][18]. Although Mg nanocomposites display excellent ductility and weight-saving characteristics, nanoparticle clusters sometimes form and reduce the strength of these nanocomposites [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…With liquid fabrication method, the preform can be infiltrated by molten magnesium alloy under a certain pressure due to the good liquidity of metal in the molten state. Liquid fabrication method can be categorised into squeeze casting, pressureless infiltration and vacuum pressure infiltration, etc., according to the pressure way [9][10][11]. In squeeze casting, molten magnesium alloy is exposed to air, so it is easy to introduce entrapped air within the composites [10].…”
Section: Introductionmentioning
confidence: 99%